On Foreigner Talk - Arakelyan, Ruzanna (Armenian Folia Anglistika, 2012)
The article sums up the main functions and characteristics of the use of a foreign language. The importance of certain changes that contribute to the perception of a foreign language has been addressed. These include slowing speech tempo, the number of pauses, clearer pronunciation, the simplification of the vocabulary, the use of the basic syntactic structures, repetition, etc. The investigation of a foreign speech is directly linked with simplification of the foreign language. Three main functions related to foreign speech are distinguished. It assists the communication process, the learning of the foreign language subconsciously and points out the attitude of the speaker towards the learners.